Pemanfaatan dan kandungan kunyit (Curcuma domestica) Sebagai Obat Dalam Perspektif Islam - Rohmah, Malika Nur (UNIVERSITAS ISLAM NEGERI MAULANA MALIK IBRAHIM MALANG, 2024)
Indonesia is a country with great potential as a producer of spices and seasonings. Among Indonesian native spices, namely Turmeric (Curcuma domestica) has antimicrobial activity. Plants have various ingredients that are beneficial to humans, both for health and industrial purposes. The Age of Apostles introduced the healing methods of classical, reliable medicine using plants. In the Al-Quran many kinds of plants are mentioned, including plants that can be eaten and used in medicine, one of which is the traditional medicinal plant, namely turmeric. The use of turmeric can also be used as a coloring agent in food. Turmeric has properties as herbal medicine and traditional medicine. Compounds contained in turmeric (curcumin and essential oils) have a role as antioxidants, antitumor, anticancer, antimicrobial, antitoxic. Traditionally turmeric is used by people in various countries to treat diseases such as diseases caused by parasitic microbes, insect bites, smallpox, abdominal pain (diarrhea, constipation, bloating), digestive disorders, liver disorders, asthma disorders, relieve itching, eliminate skin diseases, and reduce pain. Keywords: Utilization, Efficacy, Turmeric